An Improved Hungarian Algorithm for a Special Case of Unbalanced Assignment Problems (Global Journal of Science Frontier Research, 2022)
The current Hungarian approach to solving unbalanced assignment issues is based on the notion that some tasks should be delegated to fictitious or covert components, and those studies should be left unperformed. In real-world scenarios, it may be desirable to carry out all of the tasks on fundamental details. To do this, multiple tasks may be distributed to a single machine. The current research's enhanced Hungarian method for addressing unbalanced assignment challenges results in the ideal work assignment policy. An example using numbers shows how well the suggested strategy works and how effective it is. The acquired result is then likened to other current approaches to demonstrate our algorithm's superiority.